Halal violation episode: does severity and trust recovery impact negative consumption behavior? - Omar N.A.; Zainol Z.; Thye C.K.; Ahmad Nordin N.; Nazri M.A. (Emerald Group Publishing Ltd., 2024)
Indexed by WOS/ Scopus